Electrolyzed water oxygen evolution catalyst, room-temperature convenient preparation thereof and application of catalyst in synergistic degradation of wastewater
By doping sulfur and nitrogen into the nickel-iron layered double hydroxide, sulfur and nitrogen co-doping NiFe-LDHs, the problem of poor conductivity of electrolytic oxygen-analyzed catalysts is solved, and efficient OER performance improvement and green and environmentally friendly catalysts are achieved. Preparation, suitable for electrolytic water oxygen generation and degradation of contaminated wastewater.
Patent Information
- Application Number
- CN202411343157.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
The existing electrolytic oxygen-analyzed catalysts have poor conductivity during the OER process, which limits their electrocatalytic capabilities. The traditional modification methods are complex in technology, strong equipment dependence and high energy consumption, making it difficult to achieve green and efficient room temperature preparation.
Persulfate-corrosive nickel iron foam, sulfur and nitrogen in thiourea are doped into nickel iron layered double hydroxides to form sulfur-nitrogen co-doped NiFe-LDHs, improving conductivity and catalytic properties, and convenient synthesis at room temperature Methods, waste liquid can be used to degrade contaminated wastewater.
It achieves efficient OER performance improvement, reduces energy consumption and costs, simplifies the preparation process, and facilitates large-scale production. At the same time, waste liquid can be used for the coordinated degradation of polluted wastewater, realizing green and environmentally friendly catalyst preparation.
Smart Images

Figure CN119215953A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oxygen evolution catalysts, and in particular to water electrolysis oxygen evolution catalysts and their convenient preparation at room temperature and application in the coordinated degradation of polluted wastewater. Background Art
[0002] The development of human society requires the supply of fossil energy, and the consumption of fossil energy has led to energy shortages and environmental pollution. Creating a global sustainable energy system while protecting the environment is one of the most severe challenges facing mankind today. Among the many candidate new energy sources, such as solar energy, wind energy, tidal energy, etc. Renewable energy sources such as solar energy, wind energy, and tidal energy have great utilization value, but these renewable energy sources cannot be used on a large scale because they are very scattered. In other words, the extensive use of these renewable energy sources requires a suitable energy carrier. Among them, hydrogen is considered to be a good energy carrier because of its extremely high calorific value, renewable nature, and clean combustion products. The electrolysis of water to produce hydrogen has the technical advantages of relying on green and low-carbon energy, and has broad development space in the future. In particular, alkaline water electrolysis has attracted considerable attention due to its advantages such as simple electrolytic cell structure and low corrosion rate of electrocatalysts. This technology mainly includes hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). HER only needs to transfer two electrons, and OER produces oxygen through electrochemical oxidation of water. The whole process involves four electrons and is carried out through multi-step proton-coupled electron transfer. OER is very slow in kinetics, which not only increases the energy consumption of water electrolysis, but also requires a higher voltage to drive the reaction, which reduces the efficiency of hydrogen production and greatly limits the application of water electrolysis in the industrial field. Therefore, a suitable catalyst is needed to significantly reduce the reaction overpotential. Therefore, catalysts play an important role in the process of water electrolysis, so it is urgent to develop efficient, low-cost and stable catalysts.
[0003] Transition metal elements have rich valence states and various redox properties, which make them have great application potential in catalytic reactions. In particular, they can form multiple active sites in OER to promote the reaction. And transition metal OER catalysts show good stability and catalytic performance in alkaline solutions. Compared with traditional precious metal catalysts, transition metal catalysts have lower costs and wider sources, so they have greater application prospects.
[0004] Layered double hydroxides (LDHs), commonly known as hydrotalcite, are layered anionic compounds with high specific surface area, multiple active sites, rich and adjustable valence states, and strong ion exchange capacity. The composition of the main layer cations and interlayer anions of LDHs is highly adjustable, which allows LDHs to be customized as needed to optimize catalytic performance. At present, transition elements such as copper, iron, nickel, cobalt, and zinc are used in the structure of LDHs. Among them, nickel-iron-based LDHs have the advantages of high current density and good stability. Therefore, nickel-iron layered double hydroxides (NiFe-LDHs) are widely used in the field of electrocatalysis due to their excellent OER performance.
[0005] However, LDHs have poor electrical conductivity, which limits their electrocatalytic ability. In order to improve the electrical conductivity and catalytic performance of NiFe-LDHs, scientists have modified them in various ways. Generally, the electrical conductivity is improved by two methods: composite high-conductivity materials and doping with non-metallic heteroatoms. Among them, non-metallic doping generally requires a high-temperature step, and there are few reports on S and N co-doped NiFe-LDHs. More importantly, the preparation methods of LDHs modification (such as hydrothermal method, flux thermal method, plasma method, etc.) often have problems such as complex process, strong equipment dependence, high-temperature energy consumption, and environmental unfriendliness. Therefore, a green, clean, efficient, convenient, room-temperature synthesis method is needed to prepare sulfur-nitrogen co-doped NiFe-LDHs catalysts with better performance. Summary of the invention
[0006] The present invention provides an electrolytic water oxygen evolution catalyst and its convenient room temperature preparation and synergistic degradation of polluted wastewater application. The present invention uses persulfate to corrode nickel-iron foam to obtain nickel-iron layered double hydroxide and iron oxyhydroxide. During the corrosion process, sulfur and nitrogen in persulfate and thiourea are doped into the nickel-iron layered double hydroxide, so that the nickel-iron layered double hydroxide exhibits excellent performance. At the same time, the method does not rely on expensive equipment, has a short synthesis cycle, operates at room temperature, is easy to prepare on a large scale, and the waste liquid can be used to degrade pollutants in wastewater, which is green and environmentally friendly.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The invention provides a catalyst for oxygen evolution by electrolysis of water. The raw material components include: 3-12 mole parts of thiourea, 2-3 mole parts of foamed nickel iron, 0.12-1.3 mole parts of persulfate and water.
[0009] Preferably, it comprises: 5 to 12 mole parts of thiourea, 3 mole parts of nickel-iron foam, 0.5 to 1.3 mole parts of persulfate and water.
[0010] More preferably, the composition comprises: 5 to 10 mole parts of thiourea, 3 mole parts of nickel-iron foam, and 0.8 to 1.3 mole parts of persulfate and water.
[0011] More preferably, it comprises: 7 molar parts of thiourea, 3 molar parts of foamed nickel iron, and 1.1 molar parts of persulfate and water.
[0012] Preferably, the persulfate is ammonium persulfate or potassium persulfate.
[0013] More preferably, the persulfate is ammonium persulfate.
[0014] Preferably, the iron atom content of the nickel-iron foam is 20-30 at%.
[0015] Further preferably, the iron atomic content of the nickel-iron foam is 30 at %.
[0016] The invention provides a water electrolysis oxygen evolution catalyst, which comprises a nickel-iron foam base layer and sulfur-nitrogen co-doped nickel-iron layered double hydroxide and iron oxyhydroxide loaded on the surface of the nickel-iron foam base layer.
[0017] Preferably, the sum of the mass of the sulfur-nitrogen co-doped nickel-iron layered double hydroxide and the iron oxyhydroxide in the electrolytic water oxygen evolution catalyst accounts for 1 to 12%.
[0018] Preferably, the iron atom content in the nickel-iron foam base layer is 20-30 at%.
[0019] The present invention also provides a method for preparing a catalyst for oxygen evolution by electrolysis of water, comprising: at room temperature, mixing 0.12 to 1.3 molar portions of persulfate and water, and then sequentially adding 2 to 3 molar portions of foamed nickel iron and 3 to 12 molar portions of thiourea for soaking reaction.
[0020] The persulfate selected in the present invention has strong oxidizing property and oxidizes nickel-iron foam to form Ni 2+ and Fe 3+ (Formula 1-Formula 2), Ni 2+ and Fe 3+ With S2O8 2- OH generated by hydrolysis - (Formula 3) quickly reacts to form NiFe-LDHs (i.e. Ni(OH)2+Fe(OH)3, Formula 4-1); some Fe 3+FeOOH is formed (Formula 4-2). At the same time, thiourea accelerates the release of sulfur and nitrogen atoms with the assistance of persulfate, and the sulfur and nitrogen atoms are doped into the lattice of the NiFe-LDHs being formed, forming a dense layer of sulfur-nitrogen co-doped NiFe-LDHs on the surface of nickel-iron foam. As a three-dimensional porous network structure material, nickel-iron foam can provide a loose and porous carrier support for sulfur-nitrogen co-doped NiFe-LDHs, providing more space for subsequent ion exchange, and can also increase catalytic active sites, greatly improving the OER catalytic ability.
[0021]
[0022] 2(NH4)2S2O8 +Ni +Fe +4H2O = 4NH4HSO4+Ni(OH)2+Fe(OH)3 (4-1)
[0023] 3(NH4)2S2O8 + 2Fe + 4H2O = 6NH4HSO4 + 2FeOOH (4-2)
[0024] Sulfur-nitrogen co-doping can promote the surface reconstruction and lattice stress of NiFe-LDHs, thereby improving the activity of oxygen evolution reaction and improving electrochemical performance. At the same time, the modified sulfur-nitrogen co-doped NiFe-LDHs show good degradation effect in the persulfate system, which is an efficient modification strategy. Therefore, the present invention selects persulfate with strong oxidizing property, and the persulfate remaining in the waste liquid after the synthesis is completed can be used as a partial source of the persulfate degradation system for waste utilization, which is green and environmentally friendly.
[0025] In summary, the present invention utilizes sulfur-nitrogen co-doping to achieve excellent OER performance of NiFe-LDHs and achieves green and efficient production.
[0026] Preferably, the soaking reaction time is 1 to 3 minutes.
[0027] It should be understood that the reaction time of 1 to 3 minutes defined in this application is to illustrate that the reaction needs to be completed in a very short time, but 0.5 to 1 minute and 3 to 5 minutes close to this range can actually produce a catalyst with good activity. 1 to 3 minutes is just a condition that is closer to an ideal high-activity catalyst.
[0028] More preferably, the soaking reaction time is 2 minutes.
[0029] Preferably, the nickel-iron foam is sequentially treated with acid washing, water washing, acetone and ethanol.
[0030] The oxide layer on the surface of the nickel-iron foam is removed by pickling, and then it is washed with water, and the organic pollutants and water-soluble impurities on the nickel-iron foam are removed by acetone and ethanol.
[0031] Further preferably, the pickling solution is a 1M hydrochloric acid solution.
[0032] Preferably, the iron atom content in the nickel-iron foam base layer is 20-30 at%.
[0033] Preferably, the persulfate is ammonium persulfate or potassium persulfate.
[0034] The present invention also provides the use of the above-mentioned water electrolysis oxygen evolution catalyst or the water electrolysis oxygen evolution catalyst prepared by the above-mentioned preparation method in the electrolysis of water to produce oxygen.
[0035] The present invention also provides the use of the water electrolysis oxygen evolution catalyst or the water electrolysis oxygen evolution catalyst prepared by the preparation method in degrading polluted wastewater.
[0036] Preferably, the polluted wastewater is at least one of methyl orange, methylene blue and rhodamine B, and the degradation time is 1 to 5 minutes.
[0037] Therefore, the present invention has the following beneficial effects:
[0038] (1) The water electrolysis oxygen evolution catalyst formula provided by the present invention utilizes the synergistic effect of persulfate and thiourea to load a dense layer of sulfur-nitrogen co-doped nickel-iron layered double hydroxide and iron oxyhydroxide on the surface of nickel-iron foam, so that the overall water electrolysis oxygen evolution catalyst exhibits excellent OER performance.
[0039] (2) The method provided by the present invention uses persulfate to oxidize nickel-iron foam and introduces thiourea at the same time. During the process of oxidation to generate nickel-iron layered double hydroxide, sulfur and nitrogen are doped into the crystal structure of the nickel-iron layered double hydroxide to obtain sulfur-nitrogen co-doped nickel-iron layered double hydroxide, thereby achieving modification of the nickel-iron layered double hydroxide.
[0040] (3) The present invention utilizes an extremely short soaking reaction time (1 to 3 minutes) to prevent the synthesized water electrolysis oxygen evolution catalyst from being corroded and to maintain a high activity.
[0041] (4) The present invention focuses on a new method for preparing catalysts at room temperature, which reduces energy consumption costs, reduces dependence on expensive equipment, shortens the R&D cycle, facilitates large-scale preparation, and promotes the development of green catalyst preparation. At the same time, the catalyst obtained by the present invention is a monolithic structure, does not require a binder, has good conductivity, and can be directly used as an anode electrode in an alkaline electrolytic cell.
[0042] (5) The present invention utilizes persulfate as an oxidant. Since persulfate is dissolved in the liquid during the synthesis of the electrolytic water oxygen evolution catalyst, the entire synthesis of the electrolytic water oxygen evolution catalyst can be directly used as part of the persulfate degradation system to degrade polluted wastewater, which is green and environmentally friendly. That is, the electrolytic water oxygen evolution catalyst is synthesized in the process of synchronous degradation, achieving efficient synergistic degradation, saving time and effort. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the catalyst preparation process;
[0044] Figure 2 The appearance of water electrolysis oxygen evolution catalysts with different iron contents, Figure a is a blank nickel-iron foam, and Figure b is a water electrolysis oxygen evolution catalyst. From left to right, the Fe content is 0at%, 5at%, 10at%, 20at%, 30at%, and 70at%;
[0045] Figure 3 The performance diagram of the oxygen evolution catalyst for water electrolysis under different iron contents is shown in Figure 2. Ni, 5% FeNi, 1FeNi, 2FeNi, 3FeNi, and 7FeNi correspond to Fe contents of 0at%, 5at%, 10at%, 20at%, 30at%, and 70at% respectively;
[0046] Figure 4 XRD diagrams of oxygen evolution catalysts under different iron contents in water electrolysis, where Figure b is an enlarged view of Figure a, and Ni, 1FeNi, 2FeNi, 3FeNi, and 7FeNi correspond to Fe contents of 0at%, 10at%, 20at%, 30at%, and 70at% respectively;
[0047] Figure 5 The SEM images of the catalysts for oxygen evolution by electrolysis of water with different iron contents, wherein Ni, 1FeNi, 2FeNi, 3FeNi, and 7FeNi correspond to Fe contents of 0at%, 10at%, 20at%, 30at%, and 70at% respectively;
[0048] Figure 6 TEM, SAED and Mapping images of the water electrolysis oxygen evolution catalyst prepared in Example 1, wherein a to c are TEM images at different magnifications, d is a SAED image, and e to j are Mapping images corresponding to different elements;
[0049] Figure 7 The OER performance diagram of the electrolytic water oxygen evolution catalyst prepared with different structural additives, the blank is the comparative example 5 without the addition of thiourea;
[0050] Figure 8 The OER performance diagram of the oxygen evolution catalysts for water electrolysis prepared from different sulfur and nitrogen sources and different persulfates;
[0051] Fig. 9 This is the experimental phenomenon diagram when only ammonium persulfate is added;
[0052] Fig.10 This is the experimental phenomenon diagram when only thiourea is added;
[0053] Fig.11 This is the experimental phenomenon diagram after adding ammonium persulfate and thiourea;
[0054] Fig.12 This is the effect of different ammonium persulfate concentrations on the OER performance of water electrolysis oxygen evolution catalyst;
[0055] Fig.13 The figure shows the effect of different thiourea concentrations on the performance of the oxygen evolution catalyst in water electrolysis. 100%, 200%, 300%, and 400% correspond to 100%, 200%, 300%, and 400% of the molar amount of nickel iron foam, respectively.
[0056] Fig.14 The figure is the effect of self-corrosion time on the performance of OER catalyst for electrolysis of water. Figure a is the LSV curve of self-corrosion at different times, and figure b is the actual picture of corroded nickel-iron foam.
[0057] Fig.15 Figure 1 is the stability test result. Figure a is the constant current chronopotentiometry at 200 mA / cm 2 Figure a is the stability curve diagram under the current density of , Figure b is the stability curve diagram of the multi-step current method, and Figure c is the performance curve diagram before and after the stability test;
[0058] Fig.16 The diagrams of solution color change and degradation efficiency during the synergistic degradation process are shown in Figure a. The diagram of the color change of rhodamine B under shaking, Figure b. The diagram of the color change of methylene blue under shaking, Figure c. The diagram of the degradation efficiency of rhodamine B; Figure d. The diagram of the degradation efficiency of methylene blue; Figure e. The diagram of the degradation efficiency of four different common pollutants;
[0059] Fig.17 These are the performance graphs and XRD graphs of the catalyst prepared in Example 1 for synergistic degradation of pollutants after 15 hours of stability. Graph a is the LSV curve for synergistic degradation of pollutants after 15 hours of stability, and Graph b is the XRD graph for synergistic degradation of pollutants after 15 hours of stability. DETAILED DESCRIPTION
[0060] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0061] The nickel-iron foam used in this section was purchased from Jiangsu Jiayisheng Company. The foam metal parameters are 100mm*100mm, pore size 110PPI, and surface density 1700g / m 2 .
[0062] [Example]
[0063] Example 1
[0064] (1) Pretreatment of nickel-iron foam: At room temperature, nickel-iron foam (iron atomic content 30 at%) was processed into uniform small pieces of 1 cm×1 cm, and then ultrasonicated twice with 1 M HCl solution for 10 min to remove possible oxide layers, and then quickly washed with deionized water, and then ultrasonicated with acetone and ethanol for 1 min each to remove organic pollutants and water-soluble impurities, thereby obtaining pretreated nickel-iron foam.
[0065] (2) Preparation of catalyst for oxygen evolution by electrolysis of water: Take a piece of pretreated nickel-iron foam (iron content 30at%, 0.003mol) and add it to 10mL of 0.125M ammonium persulfate solution. After shaking evenly, add 0.006mol (200% of the molar amount of nickel-iron foam) of thiourea. After shaking at room temperature for 2min, take it out and wash it with deionized water and ethanol several times. The experimental schematic diagram is shown in the figure below. Figure 1 shown.
[0066] Example 2
[0067] This embodiment is basically the same as embodiment 1, except that the iron atomic content in the nickel-iron foam used is 20 at%.
[0068] Example 3
[0069] This embodiment is substantially the same as embodiment 1, except that ammonium persulfate is replaced by potassium persulfate of equal amount and concentration.
[0070] Example 4
[0071] This embodiment is substantially the same as embodiment 1, except that the concentration of ammonium persulfate is 0.0125M.
[0072] Example 5
[0073] This embodiment is substantially the same as embodiment 1, except that the concentration of ammonium persulfate is 0.05M.
[0074] Example 6
[0075] This embodiment is substantially the same as embodiment 1, except that the concentration of ammonium persulfate is 0.0875M.
[0076] Example 7
[0077] This embodiment is substantially the same as embodiment 1, except that the amount of thiourea used is 0.003 mol (100% of the molar amount of nickel-iron foam).
[0078] Example 8
[0079] This embodiment is substantially the same as embodiment 1, except that the amount of thiourea used is 0.009 mol (300% of the molar amount of nickel-iron foam).
[0080] Example 9
[0081] This embodiment is substantially the same as embodiment 1, except that the amount of thiourea used is 0.012 mol (400% of the molar amount of nickel-iron foam).
[0082] Comparative Example 1
[0083] This comparative example is substantially the same as Example 1, except that the nickel-iron foam used is replaced by nickel foam (0 at% iron atomic content).
[0084] Comparative Example 2
[0085] This comparative example is basically the same as Example 1, except that the iron atomic content in the nickel-iron foam used is 5 at%.
[0086] Comparative Example 3
[0087] This comparative example is basically the same as Example 1, except that the iron atomic content in the nickel-iron foam used is 10 at%.
[0088] Comparative Example 4
[0089] This comparative example is basically the same as Example 1, except that the iron atomic content in the nickel-iron foam used is 70 at%.
[0090] Comparative Example 5
[0091] This comparative example is substantially the same as Example 1, except that the addition of thiourea is eliminated.
[0092] Comparative Example 6
[0093] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of sodium hydroxide.
[0094] Comparative Example 7
[0095] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of sodium sulfide.
[0096] Comparative Example 8
[0097] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of urea.
[0098] Comparative Example 9
[0099] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of sodium peroxide.
[0100] Comparative Example 10
[0101] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of sodium thiosulfate.
[0102] Comparative Example 11
[0103] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of sodium thiosulfate, and ammonium persulfate is replaced by an equal amount of potassium persulfate of equal concentration.
[0104] Comparative Example 12
[0105] This comparative example is substantially the same as Example 1, except that thiourea is replaced by an equal amount of urea, and ammonium persulfate is replaced by an equal amount of potassium persulfate of equal concentration.
[0106] Comparative Example 13
[0107] (1) Pretreatment of nickel-iron foam: At room temperature, nickel-iron foam (iron atomic content 30 at%, 0.003 mol) was processed into uniform small pieces of 1 cm×1 cm, and then sonicated twice with 1 M HCl solution for 10 min to remove possible oxide layers, and then quickly washed with deionized water, and then sonicated with acetone and ethanol for 1 min each to remove organic pollutants and water-soluble impurities, thereby obtaining pretreated nickel-iron foam.
[0108] (2) Preparation of catalyst for oxygen evolution by electrolysis of water: A piece of pretreated nickel-iron foam (iron content 30 at%, 0.003 mol) was added to 10 mL of 0.125 M ammonium persulfate solution, and after shaking evenly, 0.006 mol (200% of the molar amount of nickel-iron foam) of thiourea was added. After shaking at room temperature for 2 min, the mixture was taken out and allowed to stand for 15 min, and then washed with deionized water and ethanol several times.
[0109] Comparative Example 14
[0110] This comparative example is basically the same as Example 1, except that: the mixture is shaken at room temperature for 2 minutes and then taken out and allowed to stand for 30 minutes.
[0111] Comparative Example 15
[0112] This comparative example is basically the same as Example 1, except that: the mixture is shaken at room temperature for 2 minutes and then taken out and allowed to stand for 4 hours.
[0113] Comparative Example 16
[0114] This comparative example is substantially the same as Example 1, except that the concentration of ammonium persulfate is 0.25 M.
[0115]
Performance test
[0116] 1. Effect of nickel-iron foam with different iron contents on the performance of oxygen evolution catalysts in water electrolysis
[0117] The morphologies of the electrolytic water oxygen evolution catalysts prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were compared, and a blank nickel-iron foam without any treatment was used as a blank control for comparative analysis. The results are shown in FIG. Figure 2 Observation Figure 2 It can be seen that from left to right, as the iron content in nickel-iron foam increases, the color of the electrolytic water oxygen evolution catalyst becomes darker. This phenomenon shows that nickel-iron foams with different iron contents have a great influence on the synthesis of electrolytic water oxygen evolution catalysts.
[0118] Furthermore, the OER performance of the oxygen evolution catalysts prepared in Examples 1 to 2 and Comparative Examples 1 to 4 was measured in 1M KOH. The results are as follows: Figure 3 As shown in a. Observation Figure 3 It can be seen from a that under the same current density, the performance of pure foamed Ni is the worst. As the iron atom content of foamed nickel iron increases from 5at%, 10at%, 20at% and even 30at%, the performance of the catalyst gradually improves, especially 20at% and 30at%, which show the best performance improvement. However, when the iron atom content is further increased to 70at%, the performance decreases significantly, indicating that the iron atom content has a significant impact on the performance. Therefore, it is believed that the optimal content of iron atoms is between 20at% and 30at%. And by comparing the performance with the purchased commercial Raney nickel (produced by Suzhou Baoshilai Company), it is found that the performance of the catalyst we prepared far exceeds that of commercial Raney nickel. The results are as follows Figure 3 As shown in b.
[0119] In order to determine the composition of the electrolytic water oxygen evolution catalyst, the electrolytic water oxygen evolution catalysts prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were subjected to XRD tests. Figure 4 In a, it can be found that the catalyst itself has strong peaks of nickel metal and iron metal base, and peaks of nickel-iron alloy appear in 2FeNi, 3FeNi, and 7FeNi. Figure 4 In b, by locally magnifying from 5° to 40°, it was found that the iron content in the Ni and 1FeNi samples was very low, so very little material was generated on the surface. As the iron atom content increased, very weak peaks gradually appeared, indicating that the crystal hardness of the catalyst was very low. Some characteristic peaks of the catalyst were also found. For example, the (003), (006) and (101) characteristic peaks of NiFe-LDHs, and the (110) and (111) characteristic peaks of α-FeOOH. Combining the results of XRD with the subsequent SEM and TEM analysis, it was finally confirmed that NiFe-LDHs and α-FeOOH were successfully grown in situ on the substrate of nickel-iron foam.
[0120] In order to determine the microscopic morphology of the electrolytic water oxygen evolution catalyst, the electrolytic water oxygen evolution catalysts prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were subjected to SEM testing, and the results are as follows: Figure 5 Observation Figure 5 It can be seen that, especially for 2FeNi and 3FeNi, a very dense, uniform and ultra-thin nanosheet structure is generated on the surface, which is a classic NiFe-LDHs morphology. However, for Ni and 1FeNi, it is difficult to find ultra-thin nanosheet structures on the surface, indicating that almost no effective NiFe-LDHs structure is generated on the catalyst surface. Although some ultra-thin nanosheet structures are also generated on the surface of 7FeNi, they are unevenly distributed and there is obvious agglomeration, which leads to poor performance.
[0121] In order to determine the composition and microscopic morphology of the electrolytic water oxygen evolution catalyst, the electrolytic water oxygen evolution catalyst prepared in Example 1 was subjected to TEM test, and the results are as follows: Figure 6 As shown. It was found that the TEM morphology of the catalyst was consistent with the SEM results, both of which were very typical ultra-thin nanosheet structure materials. Further, high-magnification TEM analysis was performed on it, and the typical (110) plane of NiFe-LDHs and the (120) plane of α-FeOOH were found; and in the SAED image, the (110) and (012) diffraction rings of NiFe-LDHs, as well as the (120) and (040) diffraction rings of α-FeOOH were also found. In addition, from the Mapping scan results, the distribution of Ni, Fe and O elements is very uniform, forming a very obvious S and N co-doped Mapping morphology, indicating that S and N are well doped into NiFe-LDHs and α-FeOOH.
[0122] In summary, the applicant has confirmed that an ultra-thin S, N co-doped NiFe-LDHs and α-FeOOH catalyst structure has been synthesized on a foam substrate.
[0123] 2. Effects of different sulfur and nitrogen sources and persulfate on the performance of water electrolysis oxygen evolution catalysts
[0124] The OER performance of the oxygen evolution catalysts prepared in Example 1 and Comparative Examples 3, 6, 7, and 9 was measured in 1M KOH. The results are as follows: Figure 7 shown. Figure 7 The persulfate source of the oxygen evolution catalyst in water electrolysis is ammonium persulfate. Thiourea is replaced by different other sources. These sources can act as structural additives and help form a layered structure. Figure 7 From the data in, it can be seen that thiourea is more beneficial to the formation of sulfur-nitrogen co-doped nickel-iron layered double hydroxide, making the OER performance of the water electrolysis oxygen evolution catalyst the best; other structural additives may lead to unsatisfactory doping effects of S and N due to the lack of S or N, resulting in poor OER performance.
[0125] The OER performance of the electrolytic water oxygen evolution catalysts prepared in Example 1, Example 3, Comparative Example 8, Comparative Example 10, Comparative Example 11 and Comparative Example 12 was measured in 1M KOH. The results are as follows: Figure 8 Observation Figure 8 The results show that after replacing ammonium persulfate with potassium persulfate, the OER performance of the electrolytic water oxygen evolution catalyst slightly decreased. This may be because ammonium persulfate itself contains ammonium ions, which are conducive to nitrogen doping and layered structure formation. Therefore, when ammonium persulfate is used as the persulfate source, in addition to playing the role of oxidizing ions, it can also assist in introducing N sources to facilitate the formation of the most important sulfur-nitrogen co-doped nickel-iron layered double hydroxides.
[0126] In addition, when urea is used to replace thiourea, whether combined with ammonium persulfate or potassium persulfate, it shows an OER performance significantly worse than that of Example 1. This may be closely related to the lack of S element in urea and the inability to form S and N co-doping. Similarly, when sodium thiosulfate is used to replace thiourea, due to the lack of N element in sodium thiosulfate, the ammonium ion in ammonium persulfate needs to be used as the N source, and the N source that thiourea can provide is much greater than the N source that ammonium persulfate can provide, so that S and N co-doping can be formed faster; therefore, after sodium thiosulfate replaces thiourea, its OER performance is significantly worse than that of Example 1.
[0127] 3. Synergistic effect of ammonium persulfate and thiourea
[0128] Figure 7In the blank group (Comparative Example 5), no thiourea was added, and only the data of ammonium persulfate proved that the performance of the catalyst for oxygen evolution by electrolysis of water decreased significantly after the addition of thiourea. Although ammonium persulfate also has N and S elements, thiourea plays an important role in the formation of the layered structure of nickel-iron layered double hydroxide in addition to the introduction of N and S elements, and the corrosion rate of ammonium persulfate is relatively fast. The time for the N and S elements in ammonium persulfate to enter the nickel-iron layered double hydroxide lattice is limited, and ultimately, it is impossible to generate a nickel-iron layered double hydroxide fully doped with sulfur and nitrogen, resulting in a significant decline in OER performance.
[0129] On this basis, the inventor conducted experiments to further determine.
[0130] All nickel-iron foams were treated according to the pretreatment method in Example 1.
[0131] Group A: Add the pretreated nickel-iron foam (iron content 30 at%, 0.003 mol) to 10 mL of 0.125 M ammonium persulfate. Observe the solution color and the state of the nickel-iron foam during the experiment, and record the results in Fig. 9 middle.
[0132] Group B: Add the pretreated nickel-iron foam (iron content 30 at%, 0.003 mol) to 10 mL of deionized water, and then add 0.006 mol of thiourea. Observe the solution color and the state of the nickel-iron foam during the experiment, and record the results in Fig.10 middle.
[0133] Group C: 0.006 mol thiourea and 10 mL 0.125 M ammonium persulfate were mixed to obtain a mixed solution, and the pretreated nickel-iron foam (iron atomic content 30 at%, 0.003 mol) was added to the mixed solution. The solution color and the state of the nickel-iron foam were observed during the experiment, and the results were recorded in Fig.11 middle.
[0134] When only ammonium persulfate was added, the solution turned green over time, and the nickel-iron foam did not change; when only thiourea was added, the solution and the nickel-iron foam did not change; in the mixed solution with both, the solution turned green, and after 20 minutes the solution became turbid, and the nickel-iron foam turned black. From these experimental phenomena, it can be inferred that in the absence of ammonium persulfate, the reaction between thiourea and nickel-iron foam is very weak, and doping is almost impossible. When thiourea is missing, it shows the same Figure 7 The results are consistent with those in the experiment. There is no visible change on the surface of nickel-iron foam, which indicates that the generated sulfur-nitrogen co-doped nickel-iron layered double hydroxide is less or incomplete, that is, it is impossible to generate completely sulfur-nitrogen co-doped nickel-iron layered double hydroxide.
[0135] 4. Effect of ammonium persulfate and thiourea concentrations on the performance of oxygen evolution catalysts in water electrolysis
[0136] The OER performance of the oxygen evolution catalysts prepared in Examples 1, 4, 5, 6 and Comparative Example 16 was measured in 1M KOH. The results are as follows: Fig.12 Observation Fig.12 It can be seen that the concentration of ammonium persulfate has an effect on the performance of the oxygen evolution catalyst in water electrolysis, and the best treatment effect is shown when the concentration is 0.125 M. However, it should be noted that too low a concentration of ammonium persulfate will lead to poor oxidizability and inability to achieve complete corrosion and ion oxidation, while too high a concentration of ammonium persulfate will lead to excessively rapid corrosion and uncontrollable reactions.
[0137] The OER performance of the electrolytic water oxygen evolution catalysts prepared in Examples 1, 7, 8, and 9 was measured in 1M KOH. The results are as follows: Fig.13 Observation Fig.13 It can be seen that the concentration of thiourea has little effect on the OER performance of the water electrolysis oxygen evolution catalyst. When the thiourea dosage is 200% of the molar amount of nickel-iron foam, the best treatment effect is shown.
[0138] 5. Effect of self-corrosion time on the performance of oxygen evolution catalysts in water electrolysis
[0139] The electrolytic water oxygen evolution catalysts prepared in Example 1 and Comparative Examples 13 to 15 were subjected to LSV performance test in 1M KOH. The results are as follows: Fig.14 Observation Fig.14 As a can be seen, the performance of non-corrosion is optimal, and the longer the self-corrosion time is, the worse the performance is. In the self-corrosion process, the remaining mixed solution continues to react, and the nickel-iron foam will produce brown material (iron oxide), and from XRD, it is seen that the nickel-iron foam after 4h self-corrosion, in addition to maintaining the original structure, also has obvious ferroferric oxide peak to appear, confirming that ferroferric oxide is generated, hindering the active site on the surface of sulfur-nitrogen co-doped nickel-iron layered double hydroxide, causing the electrolytic water oxygen evolution catalyst performance to decline. Thus, the reaction time of the present invention needs to be controlled to complete in a very short time.
[0140] 6. Stability test
[0141] The electrolytic water oxygen evolution catalyst prepared in Example 2 was heated at 200 mA / cm 2 The chronoamperometric test was conducted for 100 hours at a current density of 100 mA / cm. During the test, the current density was basically maintained above 90%. Subsequently, the multi-step current method test was conducted for 130 hours at a step current density. 2 , 200mA / cm 2 , 300mA / cm 2 The total time can reach more than 70 hours and then return to 100mA / cm 2 , 200mA / cm2 The original current density can be maintained, proving that the catalyst has excellent stability, and the total time is more than 120h. The current density is basically maintained above 90% during the process, and the LSV curves before and after stability are basically coincident, indicating that its performance is basically consistent, and it also proves that the prepared water electrolysis oxygen evolution catalyst has excellent electrochemical oxygen evolution stability. The above results are recorded in Fig.15 middle.
[0142] 7. Degradability test
[0143] The nickel iron foam was treated according to the pretreatment method in Example 1. During the preparation of the catalyst, 5 mL of a typical pollutant solution (rhodamine B, methylene blue, etc.) was added. After shaking at room temperature for 1 min, the color of the solution changed to colorless over time. Furthermore, a quantitative analysis of the absorbance was also performed, and it was found that it gradually dropped from 100% to 0 in a short period of time, proving that the electrolytic water oxygen evolution catalyst has a degradation effect on pollutants (rhodamine B, methylene blue, etc.). In addition, the same degradation experiment was also performed on some other typical environmental hormone pollutants. Four environmental hormones were selected for degradation experiments, namely hydroxybenzoic acid (HBA), ciprofloxacin (CIP), bisphenol A (BPA), and sulfadiazine (SDZ). While preparing the catalyst, it was quantitatively analyzed by chromatography, and it was found that these four environmental hormones could be well degraded, and even completely degraded within 60 seconds. The results are recorded in Fig.16 Observation Fig.17 It is known that the performance of the electrolytic water oxygen evolution catalyst prepared by the synergistic degradation of pollutants (Rhodamine B) does not decline, and in order to determine the composition of the electrolytic water oxygen evolution catalyst prepared in the degradation process, the prepared catalyst is characterized using an X-ray diffractometer. The catalyst prepared by the degradation is consistent with the catalyst peak position prepared in Example 1, indicating that the synthesized catalyst has not changed, or sulfur and nitrogen co-doped nickel-iron layered double hydroxide. In general, while preparing the catalyst, pollutants can also be degraded, showing that there is a good synergistic effect between the two.
Claims
1. A catalyst for oxygen evolution by water electrolysis, characterized in that The raw material components include: 3-12 mole parts of thiourea, 2-3 mole parts of foamed nickel iron, 0.12-1.3 mole parts of persulfate and water.
2. The water electrolysis oxygen evolution catalyst according to claim 1, characterized in that The persulfate is ammonium persulfate or potassium persulfate.
3. The water electrolysis oxygen evolution catalyst according to claim 1, characterized in that The iron atom content of the nickel-iron foam is 20-30 at%.
4. A catalyst for oxygen evolution by water electrolysis, characterized in that The electrolytic water oxygen evolution catalyst comprises a foamed nickel-iron base layer and sulfur-nitrogen co-doped nickel-iron layered double hydroxide and iron oxyhydroxide loaded on the surface of the foamed nickel-iron base layer.
5. The water electrolysis oxygen evolution catalyst according to claim 4, characterized in that The total mass of sulfur-nitrogen co-doped nickel-iron layered double hydroxide and iron oxyhydroxide in the electrolytic water oxygen evolution catalyst accounts for 1-12%; the iron atom content in the foamed nickel-iron base layer is 20-30 at%.
6. The method for preparing the water electrolysis oxygen evolution catalyst according to any one of claims 1 to 3 or the water electrolysis oxygen evolution catalyst according to any one of claims 4 to 5, characterized in that: include: At room temperature, 0.12-1.3 mole parts of persulfate and water are mixed, and then 2-3 mole parts of foamed nickel iron and 3-12 mole parts of thiourea are added in sequence for soaking reaction.
7. The preparation method according to claim 6, characterized in that: The soaking reaction time is 1 to 3 minutes.
8. Use of the water electrolysis oxygen evolution catalyst as claimed in any one of claims 1 to 3, or the water electrolysis oxygen evolution catalyst as claimed in any one of claims 4 to 5, or the water electrolysis oxygen evolution catalyst prepared by the preparation method as claimed in any one of claims 6 to 7 in electrolysis of water to produce oxygen.
9. Use of the water electrolysis oxygen evolution catalyst as claimed in any one of claims 1 to 3, or the water electrolysis oxygen evolution catalyst as claimed in any one of claims 4 to 5, or the water electrolysis oxygen evolution catalyst prepared by the preparation method as claimed in any one of claims 6 to 7 in degrading polluted wastewater.
10. The use according to claim 9, characterized in that The polluted wastewater is at least one of methyl orange, methylene blue and rhodamine B, and the degradation time is 1 to 5 minutes.
Citation Information
Cited By
Method for preparing sulfur-doped nickel hydroxide-based self-supporting electrolytic water anode
CN121250428A
A method of preparing a sulfur-doped nickel hydroxide-based self-supporting water electrolysis anode
CN121250428B
